EVALUATION OF USER ACCEPTANCE OF THE SAHAJA ONLINE APPLICATION USING THE TAM - Beny Prasetyo; Siti Nurdiana; Fahrobby Adnan (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: One example of the application of the use of information technology in public services is the use of SAHAJA ONLINE. SAHAJA ONLINE is a mobile-based application whose function is for the needs of Kediri Regency population document services with the aim of making it easier for the public to manage population documents and break down queues at the Kediri Regency Dispendukcapil office. There were several complaints that were felt by users, namely that there was information on the option selection feature in the moving certificate service which was difficult to understand and when resetting an account they were required to come directly to the Kediri Regency Dispendukcapil office. Despite these problems, people still use SAHAJA ONLINE in submitting population documents. With the conditions in the field, it certainly affects the acceptance of SAHAJA ONLINE. The purpose of this study was to find out what factors affect the acceptance of the SAHAJA ONLINE application at the Kediri Regency Civil and Civil Registration Office using the Technology Acceptance Model (TAM). The sample in this study were 365 SAHAJA ONLINE users. Data collected through questionnaires were analyzed using SmartPLS version 3.3.9. Based on the research results of the 10 hypotheses proposed, there are 9 accepted hypotheses. So that Information Quality, Complexity, Perceived Usefulness, Attitude Toward Using, Behavioral Intention to Use, and Actual Usage are acceptance factors of SAHAJA ONLINE.            Keywords: SAHAJA ONLINE; SmartPLS; TAM Abstrak: Salah satu contoh penerapan pemanfaatan teknologi informasi dalam pelayanan publik yaitu penggunaan SAHAJA ONLINE. SAHAJA ONLINE adalah aplikasi berbasis mobile yang fungsinya untuk kebutuhan layanan dokumen kependudukan Kabupaten Kediri dengan tujuan untuk mempermudah masyarakat dalam mengurus dokumen kependudukan dan mengurai antrian di kantor Dispendukcapil Kabupaten Kediri. Ditemukan beberapa keluhan yang dirasakan oleh para pengguna yaitu terdapat informasi pada fitur pemilihan opsi dalam layanan surat keterangan pindah yang sulit dimengerti dan saat melakukan reset akun yang diharuskan datang langsung ke kantor Dispendukcapil Kabupaten Kediri. Meskipun terdapat permasalahan tersebut, masyarakat masih tetap menggunakan SAHAJA ONLINE dalam melakukan pengajuan dokumen kependudukan. Dengan adanya kondisi dilapangan tersebut tentunya berpengaruh terhadap penerimaan SAHAJA ONLINE. Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor apa saja yang mempengaruhi penerimaan aplikasi SAHAJA ONLINE Dispendukcapil Kabupaten Kediri menggunakan Technology Acceptance Model (TAM). Sampel dalam penelitian ini adalah 365 pengguna SAHAJA ONLINE. Data yang dikumpulkan melalui penyebaran kuesioner dianalisis menggunakan SmartPLS versi 3.3.9. Berdasarkan hasil penelitian dari 10 hipotesis yang diajukan, terdapat 9 hipotesis diterima. Sehingga Information Quality, Complexity, Perceived Usefulness, Attitude Toward Using, Behavioral Intention to Use, dan Actual Usage merupakan faktor penerimaan dari SAHAJA ONLINE. Kata kunci: SAHAJA ONLINE; SmartPLS; TAM